EGFR and ERBB2 exon 20 insertion/duplication in advanced non–small cell lung cancer: genomic profiling and clinicopathologic features - Sompallae, Ramakrishna R.; Dundar, Bilge; Guseva, Natalya V.; Bossler, Aaron D.; Ma, Deqin (Frontiers in Oncology, 2023)
Background: Exon 20 (ex20) in-frame insertions or duplications (ins/dup) in EGFR and its analog ERBB2 are each detected in 1.5% of non-small cell lung cancer (NSCLC). Unlike EGFR p.L858R or ex19 deletions, ex20 ins/dup is associated with de novo resistance to classic EGFR inhibitors, lack of response to immune checkpoint inhibitors, and poor prognosis. FDA has approved mobocertinib and amivantamab for targeting tumors with this aberration but the number of comprehensive studies on ex20 ins/dup NSCLC is limited. We identified eighteen cases of NSCLCs with EGFR/ERBB2 ex20 ins/dup and correlated the findings with clinical and morphologic information including PD-L1 expression. Methods: 536 NSCLC cases tested at our institution between 2014-2023 were reviewed. A custom-designed 214-gene next generation sequencing panel was used for detecting DNA variants and the FusionPlex CTL panel (ArcherDx) was used for detection of fusion transcripts from formalin-fixed, paraffin-embedded tissue. Immunohistochemistry (IHC) for PD-L1 was performed using 22C3 or E1L3N clones. Results: Nine EGFR and nine ERBB2 ex20 ins/dup variants were identified from in equal number of males and females, fourteen were non or light smokers, and fifteen had stage IV disease. All eighteen cases were adenocarcinomas. Seven of the eleven cases with available primary tumors had acinar predominant pattern, two had lepidic predominant, and the remainder had papillary (1 case) and mucinous (1 case) pattern. Ex20 ins/dup were heterogenous in-frame 1–4 amino acids spanning A767–V774 in EGFR, Y772–P780 in ERBB2, and clustered in the loop following the C-helix and α C-helix. Twelve cases (67%) had co-existing TP53 variants. Copy number variation in CDK4 amplification was identified in one case. No fusion or microsatellite instability was identified in any case. PD-L1 was positive in two, low positive in four, and negative in eleven cases. Conclusions: NSCLCs harboring EGFR/ERBB2 ex20 ins/dup are rare and tend to be acinar predominant, negative for PD-L1, more frequent in non/light smokers, and mutually exclusive with other driver mutations in NSCLC. The correlation of different EGFR/ERBB2 ex20ins/dup variants and co-existing mutations with response to targeted therapy and the possibility of developing resistant mutations after mobocertinib treatment warrants further investigation.